(untitled) - Nakano, Russell (Boston, 2002)
This is the first book to cover every aspect of content management for the large-scale or growing site. It offers Web professionals a complete blueprint for developing, deploying, managing, maintaining, and evolving enterprise-class sites with the greatest business value -- at the lowest cost.
Keywords: Web sites,Trang web; Management,Quản lý